A Formal Theory of Action - Klonowski, Mateusz (Logic and Logical Philosophy, 2018)
Book Reviews: Janusz Czelakowski, Freedom and Enforcement in Action. A Study in Formal Action Theory, vol. 42 of the Trends in Logic book series, Springer, Dordrecht, 2015, 261 pages, Print ISBN 978-94-017-9854-9, Online ISBN 978-94-017-9855-6. DOI: 10.1007/978-94-017-9855-6.